(دراسة وتصميم منظومة اصدار كتيب المركبات الالية قسم المرور والتراخيص رقدالين) (Comprehensive Journal of Science, 2026)
The research paper revolves around designing a system for entering vehicle data and specifications, as well as owner data, for the Traffic and Licensing Department in Raqdalin, the vehicle booklet issuance unit, in order to issue the vehicle booklet electronically and archive it, in order to keep pace with the development taking place in our time, and to follow up on it, archive it within the system, and refer to it when needed.We studied the workflow system within the traffic and licensing department in Raqdalin and learned about the workflow method regarding the issuance of the car booklet in order to save time and effort, as there is no current system to follow up on such work. So we created a new system that was designed through studying it with the supervisor and the head of the traffic and licensing department in Raqdalin, so that it works within the department to store the data of the car owner and the specifications of the motor vehicle and issue it, and provides search, inquiries and reports in a timely manner. Thus, we designed a vehicle registration system in the traffic and licensing department in Raqdalin using a database (Microsoft Access 2010) to facilitate search operations and ease of handling, in addition to issuing special reports with ease and convenience.